Ventilatory settings in the initial 72 h and their association with outcome in out-of-hospital cardiac arrest patients: a preplanned secondary analysis of the targeted hypothermia versus targeted normothermia after out-of-hospital cardiac arrest (TTM2) trial - Robba, C; Badenes, R; Battaglini, D; Ball, L; Brunetti, I; Jakobsen, JC; Lilja, G; Friberg, H; Wendel-Garcia, PD; Young, PJ; Eastwood, G; Chew, MS; et al. (Springer Nature, 2022)
Purpose The optimal ventilatory settings in patients after cardiac arrest and their association with outcome remain unclear. The aim of this study was to describe the ventilatory settings applied in the first 72 h of mechanical ventilation in patients after out-of-hospital cardiac arrest and their association with 6-month outcomes. Methods Preplanned sub-analysis of the Target Temperature Management-2 trial. Clinical outcomes were mortality and functional status (assessed by the Modified Rankin Scale) 6 months after randomization. Results A total of 1848 patients were included (mean age 64 [Standard Deviation, SD = 14] years). At 6 months, 950 (51%) patients were alive and 898 (49%) were dead. Median tidal volume (VT) was 7 (Interquartile range, IQR = 6.2–8.5) mL per Predicted Body Weight (PBW), positive end expiratory pressure (PEEP) was 7 (IQR = 5–9) cmH20, plateau pressure was 20 cmH20 (IQR = 17–23), driving pressure was 12 cmH20 (IQR = 10–15), mechanical power 16.2 J/min (IQR = 12.1–21.8), ventilatory ratio was 1.27 (IQR = 1.04–1.6), and respiratory rate was 17 breaths/minute (IQR = 14–20). Median partial pressure of oxygen was 87 mmHg (IQR = 75–105), and partial pressure of carbon dioxide was 40.5 mmHg (IQR = 36–45.7). Respiratory rate, driving pressure, and mechanical power were independently associated with 6-month mortality (omnibus p-values for their non-linear trajectories: p < 0.0001, p = 0.026, and p = 0.029, respectively). Respiratory rate and driving pressure were also independently associated with poor neurological outcome (odds ratio, OR = 1.035, 95% confidence interval, CI = 1.003–1.068, p = 0.030, and OR = 1.005, 95% CI = 1.001–1.036, p = 0.048). A composite formula calculated as [(4*driving pressure) + respiratory rate] was independently associated with mortality and poor neurological outcome. Conclusions Protective ventilation strategies are commonly applied in patients after cardiac arrest. Ventilator settings in the first 72 h after hospital admission, in particular driving pressure and respiratory rate, may influence 6-month outcomes.